Control of characteristics of self-injected and accelerated electron bunch in plasma by laser pulse shaping on radius, intensity and shape - Maslov, V.I.; Bondar, D.S.; Grigorencko, V.; Levchuk, I.P.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2019)
At the laser acceleration of self-injected electron bunch by plasma wakefield it is important to form bunch with small energy spread and small size. It has been shown that laser-pulse shaping on radius, intensity and shape controls characteristics of the self-injected electron bunch and provides at certain shaping small energy spread and small size of self-injected and accelerated electron bunch. При лазерному прискоренні самоінжектованого згустку електронів плазмовим кільватерним полем важливо сформувати згусток з невеликим розкидом енергії і невеликим розміром. Показано, що профілювання лазерного імпульсу по радіусу, інтенсивності та формі контролює характеристики самоінжектованого електронного згустку і забезпечує при певному профілюванні невеликий енергетичний розкид і малий розмір самоінжектованого і прискореного згустку електронів. При лазерном ускорении самоинжектированного сгустка электронов плазменным кильватерным полем важно сформировать сгусток с небольшим разбросом по энергии и небольшим размером. Показано, что профилирование лазерного импульса по радиусу, интенсивности и форме контролирует характеристики самоинжектированного электронного сгустка и обеспечивает при определенном профилировании небольшой энергетический разброс и малый размер сгустка электронов.